USRP Based Digital Audio Broadcasting Using OFDM in Virtual and Remote Laboratory - Telagam, Nagarjuna; Sahu, Padma Charan; Panda, Sunita; Kandasamy, Nehru (International Journal of Online and Biomedical Engineering (iJOE), 2019)
Digital Audio Broadcasting (DAB) is an amazing technology, achieving its promise of certainly delivering high quality digital audio in the most vindicate mobile and fixed receiver environments. The radio signal processing capability can be provided by Universal software radio peripheral (USRP) hardware. The received signal frequency can be controlled and transmitting the signal through wireless is possible by installing NI USRP utility configuration. The programmable USRP was running the VI snippet program in block diagram panel with radio companion integrated through USB cable on windows 7 64. With the parameters such as IQ rate, transmitter gain, carrier frequency along with device name which is given as ni2901_1 the students can able to tune the radio signal. DAB technology is integrated with USRP device using prominent OFDM technique for promise delivery of high quality audio signal. DAB works under four transmission modes in this paper. In this paper RF0 module is used USRP device is connected with dual band vertical antenna with 2.4 and 5GHz frequency as Tx1. This transmitting VI snippet program will support all file formats such as.wav, mp3, etc. the intention of the paper is to transmit the real time data through long distance using DAB technology in remote laboratory. The proposed system is implemented in virtual lab so that it can be accessed by any user from anywhere. This system is successfully tested on institute of aeronautical engineering virtual lab.